The negative effects of electronic games on children. - Muadda Sulayman (College of Education for Pure Sciences, 2009)
Abstract The object of the research is explaining the negative effects of computer games on boys, and the research sample had been chose from schools pupils in the range of age between (12 to 20) years by using questionnaire which had been distributed on (100) pupils in different levels. The results of statistic analysis were referred to economical, educational, health and behavioral adverse effect. The researcher suggests two prophylactic programs to cut down the prolonged hours that the boys spend to play in front of the screens. The researcher had also got certain approaches and results to avoid the effects of these games which fill boys 'life without feeling behavioral, economical and health danger and loss of money and time.